Neuroviraler - Hansen, Ole Ertløv; Olsen, Jonas Bjørn (Academic Quarter | Akademisk kvarter, 2012)
Ole Ertløv Hansen and Jonas Bjørn Olsen Neuroviraler. (Neurovirals). Neuromarketing seeks to study people’s physical reaction to various visual and sensuous stimuli. The purpose of neuromarketing is to find consumers’ buy-button through observations of their physical reactions. More and more Danish firms see possibilities in viral marketing as a strategy and a potential in social media, where both small and large firms upload their humorous, impressive and sexy videos to attract consumers and make them distribute these messages on to other consumers. But if neuromarketing has a potential to discover the safe and efficient commercial, then how can neuromarketing be used to find the perfect viral success? This is the question that the article seeks to answer.